Adapted Shared Storybook Reading: A Study of Its Application for Children With Autism Spectrum Disorders in Home Settings. (March 2018) - Golloher, Andrea N.
This study investigated the use of an adapted shared reading protocol with three children with autism spectrum disorders (ASD) in home settings. Using a multiple baseline across participants design, this investigation replicated and extended a previous investigation by Browder et al. to children with ASD and home settings. In addition, this study was to investigate whether individual components of the intervention package contributed to its overall effectiveness. Finally, the extent to which the participating children generalized their ability to engage in adapted shared reading with the researcher to shared reading with their parents was explored. The results of the investigation indicate that the children with ASD demonstrated improvements in engagement in shared reading and these improvements generalized to shared reading with the children's parents.